Structural characterization of potato starch modified by a 4,6-a-glucanotransferase B from Lactobacillus reuteri E81 - Hassanein, Wael S.; Ispirli, Huemeyra; Dertli, Enes; Yilmaz, Mustafa Tahsin (ELSEVIER, 2023)
The recent reports have revealed that increase in amount of a-1,6 linkages by modification of potato starch with enzyme (glycosyltransferases) treatment gains slowly digestible properties to the starch; however, the formation of new a-1,6-glycosidic linkages diminish the thermal resistance of the starch granules. In this study, a putative GtfB-E81, (a 4,6-a-glucanotransferase-4,6-aGT) from L. reuteri E81 was firstly used to produce a short length of a-1,6 linkages. NMR results revealed that external short chains mostly comprised of 1-6 glucosyl units were newly produced in potato starch, and the a-1,6 linkage ratio was significantly increased from 2.9 % to 36.8 %, suggesting that this novel GtfB-E81 might have potentially an efficient transferase activity. In our study, native and GtfB-E81 modified starches showed fundamental similarities with respect to their molecular properties and treatment of native potato starch with GtfB-E81 did not remarkably change thermal stability of the potato starch, which seems to be very prominent for the food industry given the significantly decreased thermal stability results obtained for the enzyme modified starches reported in the literature. Therefore, the results of this study should open up emerging perspectives for regulating slowly digestible characteristics of potato starch in future studies without a significant change in the molecular, thermal, and crystallographic properties.
Keywords: 4,6-a-glucanotransferase; Potato starch; Formation of a-16 linkages; Molecular and thermal properties; Lactobacillus reuteri E81; SLOW DIGESTION PROPERTY; BIOCHEMICAL-CHARACTERIZATION; PHYSICOCHEMICAL PROPERTIES; ALPHA-GLUCANOTRANSFERASE; MOLECULAR-STRUCTURE; CHAIN-LENGTH; MAIZE STARCH; FT-RAMAN; ENZYME; SOURDOUGH; Biochemistry & Molecular Biology; Chemistry; Polymer Science